Implementation of Fuzzy-PD for Folding Machine Prototype Using LEGO EV3 - Wahyu S. Pambudi; Titiek Suheta (Universitas Ahmad Dahlan, 2018)
Folding machine prototype is a tool for folding clothes that used a LEGO Mindstorm EV3 and the movement of this LEGO will be controlled by using the proposed method.This research is using 2 kind of systems, first is (Proportional Integration Derrivative) and second is Fuzzy-PD. This system can improve the production efficiency especially in micro convection-based industry (UKM). This folding machine prototype has 3 folds connected to the EV3 Large Motors as actuators. PID and Fuzzy-PD control systems are used to control the position of the motor angle by reading the rotary encoder. Based on the test results with load condition at Kp=7,00; Ki=2.00; Kd=15.5,the PID control system has a rise time of 0.479s with settling time of 0.551s and overshoot value of 9,1%. While the result of Fuzzy-PD control shows the rise time is equal to 0.617s with settling time of 0.7s and overshoot value of 7.5%.